Using the Directional Analytic Signals of Magnetic Gradient Tensor to Determine Boundaries of Source - Pham Thanh, Luan; Hang, Nguyen Thi Thu; Thanh, Do Duc; Minh, Le Huy (VNU Journal of Science: Mathematics - Physics; Vol 33 No 4DO - 10.25073/2588-1124/vnumap.4226, 2017)
The analytic signals of the magnetic tensor gradient within two- and three-dimensional space domain can be applied as a useful tool to estimate the depth and position of magnetic sources  because their values only depend on location but not on magnetization direction of the sources of the magnetic anomaly. In this paper, we present results of the study for application of the combination of derivatives of directional analytic signals of the magnetic tensor gradient and maximum horizontal gradient to determine the edges of the sources through the Edge-Detector function (|ED|). Algorithms and programs written in the Matlab language have been used for testing the calculation on 3D models in correlative comparison with the method using the amplitude function of analytic signals. The calculation results showed the advantages of the |ED| function and its applicability in determing the boundaries of sources of magnetic anomaly.